ALLOPHONIC FEATURES OF INTERNET COMMENTS IN ENGLISH AND UZBEK - Abidova Shoxida Murodovna, (TADQIQOTLAR, 2025)
Abstract: The rapid development of digital communication has significantly influenced spoken and written language forms, particularly in online environments. Internet  comments  represent  a  unique  linguistic  space  where  features  of  spoken language are reflected in written form. This article investigates the allophonic features observed in internet comments in English and Uzbek. The study aims to identify how phonetic  variations,  sound  substitutions,  and  informal  pronunciation  patterns  are represented orthographically in online comments. Using a comparative approach, the research analyzes samples of internet comments from social media platforms in both languages.  The  findings  reveal  both  language-specific  and  universal  tendencies  in allophonic representation, influenced by phonological systems, sociolinguistic factors, and digital communication norms.